Pengaruh Tingkat Kesehatan Bank Terhadap Pertumbuhan Laba Perusahaan Perbankan Yang Terdaftar Di BEI 2015-2019 - Samosir, Hotris; Siregar, Retnawati; Sari, Warsani Purnama (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
Abstract This study aims to determine partially and simultaneously the effect of CAR (X1), NPL (X2), NPM (X3), ROA (X4), and LDR (X5) on profit growth (Y). This type of research is associative. The population in this study were all banking companies listed on the Indonesia Stock Exchange as many as 43 banking companies and the samples in this study were 10 banking companies. The criteria for the companies that are sampled in this study are companies that publish financial statements for 5 years, namely the 2015- 2019 period and have been audited. The type of data used in this research in quantitative data. Sources of data used in this study is secondary data. The data collection technique used by the researcher is documentation. This study use multiple analysis tehcniques with the help of SPSS. The result of the test can be seen that the partial test on the variabel CAR, NPL, LDR has a significant positive effect on profit growth, while the NPM, and ROA variables have no effect on profit growth. Based on the simultaneous F test that all variabels X namely CAR, NPL, NPM, ROA, LDR simultaneously have a significant positive effect on profit growth and can be seen from the adjusted R Square value obtained by 95%.slotvm777ladang78 slot loginladang78 slot loginladang78 loginladang78 slot loginladang78Ladang78Ladang78Jawa88Jawa88Royal88ladang78Jawa88Jawa88